A comparison of the effects of topical treatment of calcipotriol, camptothecin, clobetasol and tazarotene on an imiquimod-induced psoriasis-like mouse model. (February 2014) - Sun, Jun; Dou, Wei; Zhao, Yi; Hu, Jinhong
Abstract The interleukin-23/interleukin 17A (IL-23/IL-17A) cytokine axis plays a critical role in the pathogenesis of psoriasis. In this study, we report the effects of topical calcipotriol, camptothecin, clobetasol and tazarotene on the treatment of imiquimod (IMQ)-induced psoriasis-like inflammation, the development of which is dependent on the IL-23/IL-17A axis. IMQ-induced epidermal hyperplasia and inflammation in the BALB/c mouse ear were significantly inhibited following clobetasol treatment but not calcipotriol, camptothecin or tazarotene treatments. Real-time polymerase chain reaction showed that the mRNA levels of IL-17A, IL-17F, IL-22, IL-1β, IL-6 and TNF-α in ear skin were significantly decreased by clobetasol. In addition, we observed that calcipotriol, camptothecin and tazarotene failed to show any inhibitory effects on the IL-23/IL-17A/IL-22 axis. We also found that clobetasol treatment inhibited the proliferation of γδ T cells and C-C chemokine receptor type 6 (CCR6) expression induced by IMQ. Calcipotriol, camptothecin and tazarotene not only failed to inhibit this proliferation but also enhanced retinoic acid-related orphan receptor γ (RORγ) expression in IMQ-induced psoriasis-like inflammation. In conclusion, we suggest that clobetasol induces the relief of IMQ-induced psoriasis-like inflammation in a mouse model but that calcipotriol, camptothecin and tazarotene cannot. Therefore, we suggest that more in-depth studies on pharmacological effects of tazarotene, camptothecin and calcipotriol should be carried out.